PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT INTI BARA PERDANA (IBP) TABA PENANJUNG BENGKULU TENGAH - Arnoldi, Arnoldi; Ekowati, Sri (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2024)
This study aims to determine the effect of leadership style and work environment on employee performance at Pt Inti Bara Perdana (IBP) Taba Penanjung Central Bengkulu, either partially or simultaneously. The sample in this study was 85 respondents, the data collection method used was Total Sampling. Data collection techniques with observation and questionnaires, data analysis techniques with multiple linear regression. The tcount for the Leadership Style Variable for the Leadership Style variable is 9,305 which means that there is a positive influence between Leadership Style on Employee Performance at PT Inti Bara Perdana (IBP) Taba Penanjung Bengkulu Tengah. Work Environment Variable The tcount value for the Work Environment variable is 2,342, which means there is a positive influence between the Work Environment and the Decision to Visit PT Inti Bara Perdana (IBP) Taba Penanjung Bengkulu Tengah. Based on the results of calculations using SPSS, the F test was used to test the coefficients as a whole by using a significant level of 0.05 to obtain a Fsig of 0.000 while the calculated F value was 49,241, this indicates that Ho is rejected and Ha is accepted, thus the overall influence variable namely Leadership Style and Work Environment have a significant and positive influence on Employee Performance at PT Inti Bara Perdana (IBP) Taba Penanjung Bengkulu Tengah. Keywords: Leadership Style, Work Environment, and Employee Performance